IMPLEMENTASI AKUNTANSI FORENSIK DAN AUDIT INVESTIGASI DALAM MENDETEKSI FRAUD DI LINGKUNGAN DIGITAL: (Survey pada Media Elektronik Di Indonesia) - Nahruddien Akbar. M (IKOPIN, 2019)
The purpose of this study to find out how forensic accounting and investigative audits applied in detecting fraud in the environment Digita. The research method with qualitative methods, the primary type of data used, the results of interviews with internal auditors and investigation to strengthen research, conducted interviews with 3 internal auditors and investigations. Data analysis technique used is qualitative data analysis techniques with descriptive approach.The results of this study indicate that the forensic accounting in detecting fraud in the digital environment can be made by Computer Forensic and investigation should be done is to make Copies of all log data, create Fingerprint of the data mathematically, making Fingerprint of Copies, making Hashes Masterlist and documentation of data has worked. Reasons forensic accounting and investigative audits applied to secure and analyze digital evidence. Another reason is to eradicate fraud in the digital environment